Theoretical and numerical study of the time-bandwidth product in resonant cavities with nonreciprocal coupling - Cardea, I.; Grassani, D.; Upham, J.; Boyd, R.W.; Schulz, S.A.; K. L. Tsakmakidis; Brès, C.S. (Optics InfoBase Conference Papers, 2020)
We present a theoretical and numerical model to show how the nonreciprocal coupling in a generalized resonator affects the balance between the reflected and intracavity power as well as the time-bandwidth product of the system. © OSA 2020 © 2020 The Author(s)